The impact of ESG reporting on the implementation of professional ethical standards among employees of commercial banks in Vietnam - Thu, Ha Do Thi; Minh, Anh Le (Edelweiss Applied Science and Technology, 2025)
In the context of sustainable development and global integration, ESG standards (Environmental, Social, and Governance) are gradually becoming mandatory requirements for the banking system. This study aims to examine the relationship between the level of ESG reporting implementation and compliance with professional ethical standards among employees in Vietnamese commercial banks (CBs). Based on a survey of 380 banking employees from various CBs and the application of Ordinary Least Squares (OLS) linear regression to analyze the Environmental, Social, and Governance factors, the research reveals that the Environmental factor has the strongest impact on the implementation of ethical standards. The Governance factor also positively influences employees’ ethical behavior, whereas the Social factor shows no significant impact on their ethical standards. This indicates that ESG reporting is not merely a disclosure requirement but plays a substantive role in enhancing the ethical culture and internal capacity of credit institutions. The findings provide practical foundations for CBs to improve the effectiveness of ESG implementation and offer valuable implications for future research.